The role of women in cultivating sustainable societies through millets - Kumar, Raghvendra 1987-; Priyadarshini, Ishaani 1992- (IGI Global, 2024)
Millets are ancient grains that have been cultivated by humans for centuries, and they have recently emerged as a crucial staple food in numerous cultures owing to their abundant essential nutrients and their resilience to changing climates, requiring fewer resources for growth. In the face of the current climate crisis, the spotlight on millets as a cornerstone of sustainable societies has intensified.The Role of Women in Cultivating Sustainable Societies Through Millets delves into the significance of millets in sustainable agriculture and the indispensable role that women play in their cultivation and promotion. This book seeks to advocate for the cultivation and consumption of millets as a pathway to constructing sustainable societies. However, it goes beyond mere cultivation, as it critically recognizes and highlights the pivotal role of women in this transformative process. Drawing from millennia of historical perspectives, the book examines how women have been key agents of change in millet cultivation, shaping its cultivation techniques, preservation, and the propagation of traditional knowledge across generations. To further solidify the book's foundation, it includes compelling case studies, illustrating successful real-world applications of millet cultivation and its socio-economic impact, making this book a timely and essential resource for students, researchers, academicians, and industry professionals alike.